Developing the System of Child Protection and Child-friendly Justice: Models of Analysis, Research Approaches and Successful Practices - Chirkina R.V (Moscow State University of Psychology and Education, 2016)
One of the main objectives of National Strategies on developing the system of children safeguarding and child-friendly justice is the establishment an effective system of prevention of offenses committed against minors and minor offences, as well as child-friendly justice and penal system. The article describes the issue of performing the task of creating a child-friendly justice, analyzes approaches to accomplish the tasks that can be implemented only in cooperation with different departments and agencies. Author considers the successful practices developing National Strategy provisions throughout the country, and provides analysis models of prevention of child delinquent behavior and neglect. The paper focuses on system analysis as a method of forecasting and overcoming dysfunctionality and system links irregularities in the field of minors social problems solving. Article proposals on development of the missing elements in the system of prevention and the implementation of the National Strategy provisions.